2013
DOI: 10.1037/a0032060
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between working memory capacity and broad measures of cognitive ability in healthy adults and people with schizophrenia.

Abstract: Objective Working memory (WM) capacity, typically measured with cognitively complex span tasks, is correlated with higher-order cognitive abilities in healthy adults. The goals of the present study were to determine: 1) if a more focused measure of visual WM storage capacity would show similar higher-order ability correlations in healthy adults and in people with schizophrenia (PSZ) thereby demonstrating the importance of simple storage capacity, 2) determine if the illness alters the pattern of correlations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
159
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(172 citation statements)
references
References 65 publications
10
159
3
Order By: Relevance
“…We used a change localization task to assess visual WM capacity. Our version of this task 16 presents participants with an array of 4 colored squares, each with a visual angle of 0.7° × 0.7°. The stimuli are arranged around an invisible circle with a radius of 3° for 100 ms, with 1 square in each quadrant of the screen and at least 2.33° of visual angle separation from the next square.…”
Section: Methodsmentioning
confidence: 99%
“…We used a change localization task to assess visual WM capacity. Our version of this task 16 presents participants with an array of 4 colored squares, each with a visual angle of 0.7° × 0.7°. The stimuli are arranged around an invisible circle with a radius of 3° for 100 ms, with 1 square in each quadrant of the screen and at least 2.33° of visual angle separation from the next square.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the vast storage in human long-term memory, WM has been demonstrated to have a capacity limited by the number of items [8,9] and this is strongly correlated with general cognitive ability [10,11] . Recent advances in studying visual WM have shown a precision limit of representations in WM besides the capacity limit [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…However, with regard to WM the role of the delay activity in sensory cortices has been thought to differ from that of the PFC. The former has been thought to represent and store selective sensory information and the latter has been considered to exert attentional bias and cognitive control over the former (see reviews [6,7] ).Despite the vast storage in human long-term memory, WM has been demonstrated to have a capacity limited by the number of items [8,9] and this is strongly correlated with general cognitive ability [10,11] . Recent advances in studying visual WM have shown a precision limit of representations in WM besides the capacity limit [12][13][14][15][16] .…”
mentioning
confidence: 99%
“…It may be that this imperviousness to training is due to the fact that change detection, unlike other WM tasks used for training that incorporate sequential processing and/or combine processing and storage components, targets the ability to store multiple items simultaneously. Despite this rather pessimistic outlook on the trainability of change detection, improving change-detection performance could be desirable because it has repeatedly been demonstrated that WM capacity as measured with a changedetection paradigm correlates well with measures of intelligence (e.g., Cowan et al 2005;Cowan et al 2006;Johnson et al 2013). More specifically, it has been shown that it is the number of representations that can be held simultaneously in WM that mediates the relationship between change-detection performance and intelligence (Fukuda et al 2010).…”
Section: Introductionmentioning
confidence: 99%